3D printing of in-situ curing thermally insulated thermosets. (August 2019) - Wang, Biran; Arias, Kristen F.; Zhang, Zimeng; Liu, Yuchen; Jiang, Zhiyuan; Sue, Hung-Jue; Currie-Gregg, Nancy; Bouslog, Stan; Pei, Zhijian (Z.J.); Wang, Shiren
Abstract: This research reports additive manufacturing of in-situ curing thermosets using direct ink-writing (DIW) process. The investigation reveals the relationships between printing process parameters, such as extrusion pressure and operating temperature, and the resultant morphology and thermal conductivity. With the decrease of printing pressure from ∼125 to ∼25 mbar, crisscross structure appeared along with phonon boundary scattering effect which then causes ∼33% reduction in thermal conductivity from ∼0.12 Wm −1 K −1 to ∼0.08 Wm −1 K −1 . The optimal cured temperature is found to be 75 °C, which yields thermal conductivity of ∼0.1 Wm −1 K −1 (∼33% decrease compared to the sample cured at 70 °C) without increase the roughness of the printed surface.